Depside α-Glucosidase Inhibitors from a Culture of the Mushroom Stereum hirsutum - Wang, Bo Tao; Qi, Qiu Yue; Ma, Ke; Pei, Yun Fei; Han, Jun Jie; Xu, Wei; Li, Er Wei; Liu, Hong Wei (Planta Medica, 2014)
Nine new isoprenylated depsides, sterenins E–M (1–9), as well as five known compounds (10–14), were isolated from the solid culture of Stereum hirsutum. The structures of the new compounds were elucidated by spectroscopic methods. Their inhibitory activities against yeast α-glucosidase were evaluated in vitro. Compounds 1–4 and 7–14 showed inhibitory activities with IC50 values of 7.62, 3.06, 6.03, 22.70, 36.64, 13.09, 27.52, 25.10, 12.32, 3.31, 23.82, and 14.17 µM, respectively. Compounds 5 and 6 showed no inhibitory activities with IC50 values higher than 50 µM. Therefore, the culture of S. hirsutum and its secondary metabolites could have a potential usage for the development of hypoglycemic drugs.
Keywords: Stereum hirsutum; Stereaceae; isoprenylated phenols; structure elucidation; glucosidase inhibition